Generation of Ultraintense Proton Beams Driven by a Short-Pulse Multi-TW Laser - Badziak, J.; Jabłoński, S.; Parys, P.; Rosiński, M.; Wołowski, J.; Szydłowski, A.; Antici, P.; Fuchs, J.; Mancic, A. (Photonics Letters of Poland, 2009)
The results of experimental studies of high-intensity proton beam generation at the interaction of a 350 fs laser pulse of 1.06um or 0.53um wavelength and intensity up to 2×1019Wcm-2 with a thin (0.6-3um) solid target are reported. It is shown that collimated MeV proton beams of intensity ~ 1018Wcm-2 and current density ~ 1012Acm-2 at the source can be produced when the laser-target interaction conditions approach the skin-layer ponderomotive acceleration requirements and the laser intensity-wavelength product is above 109Wcm-2um2. The effect of laser intensity, the target structure and the laser wavelength on the proton beam intensity and the laser-protons energy conversion efficiency are demonstrated. Full Text: PDF References: G.Mourou and D.Umstadter, Sci.Am. 286, 80 (2002). L.Robson, et al., "Scaling of proton acceleration driven by petawatt-laser–plasma interactions", Nature Phys. 3, 58 (2007). [CrossRef] M. Borghesi, et al., Fusion Sci. Technol. 49, 412 (2006) and references therein. J. Badziak,"Laser-driven generation of fast particles", Opto-Electron. Rev. 15, 1 (2007) and references therein. [CrossRef] K.W.D. Ledingham, P. McKenna and R. Singhal,"Applications for Nuclear Phenomena Generated by Ultra-Intense Lasers", Science 300, 1107 (2003) and references therein. [CrossRef] A. Maksimchuk, et al.," High-energy ion generation by short laser pulses", Plasma Phys. Rep. 30, 473 (2004). [CrossRef] S.V. Bulanov, et al.," Oncological hadrontherapy with laser ion accelerators", Phys. Lett. A 299, 240, 2002. [CrossRef] M. Koenig, et al.,"Progress in the study of warm dense matter", Plasma Phys. Control. Fusion 47, B441 (2005). [CrossRef] P.K. Patel, et al.,"Isochoric Heating of Solid-Density Matter with an Ultrafast Proton Beam", Phys. Rev. Lett. 91, 125004 (2003). [CrossRef] M. H. Key, et al., Fusion Sci. Technol. 49, 440 (2006) and references therein. J. Badziak, S. Jabłoński and J. Wołowski," Progress and prospect of fast ignition of ICF targets", Plasma Phys. Control. Fusion 49, B651 (2007) and references therein. [CrossRef] F. P. Boody, et al.,"Laser-driven ion source for reduced-cost implantation of metal ions for strong reduction of dry friction and increased durability", Laser Part. Beams 14, 443 (1996). [CrossRef] S. Fritzler, et al.," Proton beams generated with high-intensity lasers: Applications to medical isotope production", Appl. Phys. Lett. 83, 3039 (2003). [CrossRef] S.C. Wilks, et al.," Energetic proton generation in ultra-intense laser–solid interactions", Phys. Plasmas, 8, 542 (2001). [CrossRef] R.A. Snavely, et al.,"Intense High-Energy Proton Beams from Petawatt-Laser Irradiation of Solids", Phys. Rev. Lett. 85, 2945 (2000). [CrossRef] B.M. Hegelich, et al.," Spectral properties of laser-accelerated mid-Z MeV/u ion beams", Phys. Plasmas 12, 056314 (2005). [CrossRef] P. McKenna, et al.," Low- and medium-mass ion acceleration driven by petawatt laser plasma interactions", Plasma Phys. Control. Fusion 49 B223 (2007). [CrossRef] J. Badziak, et al.,"http://dx.doi.org/10.1088/0741-3335/49/12B/S20", Appl. Phys. Lett. 85, 3041 (2004). [CrossRef] J. Badziak, et al.,"Laser-driven generation of high-current ion beams using skin-layer ponderomotive acceleration", Laser Part. Beams 23, 401 (2005). [CrossRef] J. Badziak, S. Jabłoński, and S. Głowacz," Generation of highly collimated high-current ion beams by skin-layer laser-plasma interaction at relativistic laser intensities", Appl. Phys. Lett. 89, 061504 (2006). [CrossRef] T. V. Liseykina and A. Macchi, Appl. Phys. Lett. 91, 171702, (2007). J. Badziak, et al.,"Studies on laser-driven generation of fast high-density plasma blocks for fast ignition", Laser Part. Beams 24, 249 (2006). [CrossRef] J.Badziak and S.Jabłoński," Focusing of high-current laser-driven ion beams", Appl. Phys.Lett. 90, 151503 (2007). [CrossRef] J. Fuchs, et al.," Comparative spectra and efficiencies of ions laser-accelerated forward from the front and rear surfaces of thin solid foils", Phys. Plasmas 14 053105 (2007). [CrossRef] J. Badziak, et al.," Intensity-dependent characteristics of a picosecond laser-produced Cu plasma", J. Phys. D: Appl. Phys. 34, 1885 (2001). [CrossRef] A. Szydłowski et al.," Advantage of PM-355 nuclear track detector in light-ion registration and high-temperature plasma diagnostics", Radiat. Meas. 34, 325 (2001). [CrossRef] H. Habara, et al.," Momentum distribution of accelerated ions in ultra-intense laser–plasma interactions via neutron spectroscopy", Phys. Plasmas 10, 3712 (2003). [CrossRef]